Agricultural machinery supply businesses in Myanmar's dry zone: Growth and transformation - Belton, Ben; Fang, Peixun; Abaidoo, Eric (Michigan State University, 2019)
This report presents findings on the supply side of agricultural mechanization in Myanmar, based on a survey of 57 agricultural machinery suppliers in five urban centers in Myanmar’s Central Dry Zone, and incorporating information on the location and year of establishment of branches of machinery businesses based in Yangon. Key findings are summarized below. Machinery supply businesses are now numerous and widely distributed. Fifty-seven enterprises were identified, operating a total of 234 stores in 74 townships and 13 states/regions. Ownership is quite concentrated, with six businesses accounting for 52% of all stores. All enterprises surveyed are Myanmar owned and operated. Most were established in order to supply agricultural machines or other heavy machinery, but a few of the largest have since diversified into other sectors. The main rice growing zones of the Delta and Dry Zone were the first to begin to mechanize, with mechanization subsequently spilling over into areas of the Dry Zone growing non-rice crops, and to upland areas. Numbers of agricultural machinery supply shops in Myanmar increased 333% between 2008 and 2018, from 54 to 234, while the number of townships with machinery suppliers jumped from 29 to 74. Numbers of agricultural machinery supply outlets in the Dry Zone grew slowly until 2013. Very rapid growth took place from 2014-2017, during which 61% of all stores were established. Half (49%) of all machinery supply business are located in the Dry Zone, 36% in the Delta and 15% in the hilly and border states. Sales of agricultural machinery in the Dry Zone boomed from 2013-2016, increasing several fold, but growth peaked by 2017. Sales of four-wheel tractors and combine harvesters contracted slightly in 2017, by -22% and -16% respectively. Sales of two-wheel tractors and attachments for four-wheel tractors also fell in 2017. A wider assortment of agricultural equipment is now available from a greater range of sources than ever before. The proliferation of businesses has created opportunities for numerous brands to enter the marketplace as both suppliers and manufacturers compete for market share. The number of four-wheel tractor brands sold quadrupled from 2013 to 2017, while the number of combine harvester brands available doubled from 2015 to 2017 Products sold by businesses in the Dry Zone reflect the agro-ecology of the region. Four-wheel tractors and their attachments (disc plows and rotary tillers) are the main items, outselling two-wheel tractors, water pumps, and engines, which are the highest volume items sold in the Delta. Very low sales of water pumps in the Dry Zone reflect limited direct access to irrigation canals and ground water. Dry Zone farmers prefer four-wheel tractors for non-paddy crops because two-wheel tractors have insufficient power to break up hardened soils prior to cultivation. In the Delta, where paddy is the dominant crop and water is plentiful, soils are softened by puddling before paddy cultivation commences, making two-wheel tractors better suited to plowing than heavy four-wheel tractors. Finance for agricultural machinery purchases is widely available and utilized, contributing the rapid growth of machinery sales. Almost all machinery supply businesses offer some form of hire purchase financing. The importance of banks as a source of finance has grown relative to that of direct finance provided by machine suppliers. The share of machinery suppliers partnering with banks to provide hire purchase loans to customers buying two-wheel tractors, four-wheel tractors, and combine harvesters increased from little or nothing before 2013, to 84%, 87% and 96%, respectively in 2017. Sales financed through hire purchase loans supplied by banks are reported to account for 76%, 67% and 98% of sales of these machines, respectively. The number of banks offering hire purchase loans for agricultural machinery has increased quickly, from five in 2014 to 11 in 2017. Throughout this period two banks, Yoma and MCB, dominated the provision of hire purchase finance. Yoma accounted for 41% of partnerships with machinery dealerships in 2014, rising to 48% in 2017. Almost all purchases of agricultural machines and attachments are initiated by customers, except for four-wheel tractors. One quarter of four-wheel tractors purchases made in 2017 were organized by co-operative associations under the Department of Co-operatives, or brokered by the Agricultural Mechanization Department. The benefit of government agents acting as intermediaries between buyers and sellers of machinery is not clear, given that sales of all machines other than four-wheel tractors are made almost exclusively via direct customer-supplier interaction.